The reflective cognitive style and its relationship to the mental development of university students (Journal of the College of Basic Education, 2022)
The pace of development of societies has been associated with and greatly influenced by the increasing growth of scientific discoveries, and in order to keep up with this increasing growth, it has become necessary for man to use mental processes in a growing cognitive manner because of its association with mental development.